Professional objectives of higher education: Imbalances and adaptation - Voronkova Elena Konstantinovna (EDP Sciences, 2021)
This article analyzes the systemic issues of personnel education in higher education, reveals their causes and consequences. Qualitative and quantitative characteristics of university graduates are one of the conditions for the state economic development. The goals and objectives of higher education should meet the needs of the state, industries, regions, and business. The lack of strong signals from consumers of educational services creates an imbalance between the higher education system and the market requirements and results in the conservatism of higher education. In this context, the purpose of this article is to develop a conceptual model for assessing the contribution of higher education to the national economy as one of the drivers of its transformation. The need to optimize the professional structure of education, with reference to the potential and prospects of the national economy, is emphasized. Research methods involve analysis and synthesis, induction and deduction, system and logical methods. The study result is a model that takes into account a number of indicators of employer satisfaction in university graduates, as well as indicators of regional and industrial security of specific professionals with higher education. An effective motivation for employers to take a more active part in the organization of higher education is the system of educational loans. The state’s management of the credit sphere creates opportunities for consumers of educational services to direct financial flows primarily to education in priority specialties. The effectiveness of this tool requires ensuring its accessibility to employers and differentiating interest rates.